2010
DOI: 10.1523/jneurosci.3025-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Meningeal Excitability Mediated by Corticotrigeminal Networks: A Link for the Endogenous Modulation of Migraine Pain

Abstract: Alterations in cortical excitability are implicated in the pathophysiology of migraine. However, the relationship between cortical spreading depression (CSD) and headache has not been fully elucidated. We aimed to identify the corticofugal networks that directly influence meningeal nociception in the brainstem trigeminocervical complex (Sp5C) of the rat. Cortical areas projecting to the brainstem were first identified by retrograde tracing from Sp5C areas that receive direct meningeal inputs. Anterograde trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
81
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 35 publications
11
81
0
Order By: Relevance
“…1,[9][10][11][12][13][14][15][16] This is supported by several lines of evidence. First, animal studies report light-aversive behaviors in neonatal rodents before rod/cone development, but an absence of these behaviors in melanopsin knockout mice.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…1,[9][10][11][12][13][14][15][16] This is supported by several lines of evidence. First, animal studies report light-aversive behaviors in neonatal rodents before rod/cone development, but an absence of these behaviors in melanopsin knockout mice.…”
supporting
confidence: 52%
“…23 Fourth, ipRGCs project directly to pain centers in the posterior thalamus where afferent retinal inputs converge with the trigeminal nociceptive pathway. 9,10 Collectively, there is accumulating evidence showing that the ipRGC pathway is the primary transducer of photophobia.…”
mentioning
confidence: 99%
“…In addition, several studies have reported that myofascial trigger points could reproduce migraine symptoms 37,38 , Moreover, an increasing amount of evidence shows that dyscoordination between the dorsal horns of the upper cervical spinal cord and trigeminal nucleus caudalis may induce cervicogenic headaches. The prolonged irritated inputs implicate in the pain processing through trigeminovascular system, which can provoke and worsen the symptoms of migraine 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Although this study raised deep criticism for a possible suboptimal study design [33], two direct anatomical topdown projections to trigeminal nuclei have been very recently described [34]. The first, associated with facilitatory effects, directly links a specific insula area to trigeminovascular neurons located in I and II laminae.…”
Section: New Evidences On the Cortical Spreading Depression Role In Mmentioning
confidence: 91%